A Discursive Representation of Reporter ‘Shireen Abu Akleh’ during Conflict between Palestine & Israel - Lukman Hakim (Nusantara Journal of Multidisciplinary Science, 2024)
The death of Al-Jazeera reporter Shireen Abu Akleh on May 11, 2022, left the public uncertain whether she was intentionally targeted by the Israeli army or killed by Palestinian gunfire. This study investigates the discursive representation of Shireen Abu Akleh, Palestinians, and Israeli soldiers during the conflict through the lens of critical discourse analysis (CDA) as outlined by Fairclough, encompassing the three stages of description, interpretation, and explanation. The analysis reveals that both Al-Jazeera and BBC News constructed a positive identity for Shireen Abu Akleh. However, BBC News notably emphasized her death as a consequence of her role as a reporter. Al-Jazeera explicitly attributed responsibility for her death to Israelis, whereas BBC News highlighted portrayals of Palestinians as terrorists and uncooperative. This demonstrates online media biases, subtly favoring the villains while showcasing how discourse shapes societal perceptions of justice and truth